ANALISIS KESTABILAN LERENG DINDING AKHIR DI PIT BARATLAUT PADA PENAMBANGAN BATUBARA DI PT. PUTERA BARA MITRA , KECAMATAN MENTEWE, KALIMANTAN SELATAN - Untung Wahyudi; Excelsior T P; Luthfi Wahyudi (KURVATEK, 2018)
PT. Putera Bara Mitra used open mining system for mining operation, Yet the completion of study on the end wall slope stability that  undertaken by geotechnical PT. Putera Bara Mitra in Northwest Pit and the occured a failure in the low wall on the 1st June 2012 led to the need for analysis and design the overall slope at the mine site. To analyze and design the overall slope, used value of the recommended minimum safety. The value was based on company for single slope SF ≥ 1.2 and SF ≥ 1.3 for overall slope. The calculation used Bichop method with the help of software slide v 5.0. Geometry improvements was done at the low slopes that originally single wall with a 30 m bench height and a slope 70° with SF = 0.781, into 4 levels with SF = 1.305. The analysis explained the factors that affect the stability of the low wall included the mining slope geometry, unfavorable drainase system, material stockpiles and seismicity factors. It was necessary to do prevention efforts to maintain the stability of the slope included the redesign to slope geometry, handling surface and subsurface water in a way to control slopes draining groundwater, vegetation stabilization using and monitoring slope using Total Station with Prism and Crackmeter to determine the movement of cracks visible on the surface.